Nursing students’ knowledge and perception regarding self-neglect in elderly at School of Health Sciences, Universiti Sains Malaysia - Din, Muhammad Arrasyid (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Self-neglect is a worrying phenomenon that mainly occurs in elderly population. Study found that the most significant barrier to intervene self-neglect in elderly is the incomplete understanding of the phenomenon that continues despite the consistency of self-neglect research. Since nursing students are the future healthcare providers for the elderly population, the need of nursing students with the positive perception, adequate knowledge and skill are crucial in protecting and enhancing the health of this vulnerable population. Thus, a cross-sectional study was carried out to study the nursing students’ knowledge and perception regarding self-neglect in elderly at School of Health Sciences, USM. The questionnaire used in this study was a selfadministered questionnaire consist of 9 questions on knowledge and 16 questions on perception regarding self-neglect in elderly. A total of 111 nursing students in School of Health Sciences, USM who fulfilled the inclusion and exclusion criteria were selected purposively. Data collected were statistically analyzed using the SPSS software version 25.0. Pearson Chi-Square test has been used for data analysis. The finding revealed that nursing students at School of Health Sciences, USM have a high level of knowledge (n= 87, 77.7%) and positive perception (n= 84, 75.7%) toward elderly. Despite a statistically insignificant between family type and living experience with an elderly member, majority of the nursing students who lived in nuclear family and those who had living experience with an elderly member reported themselves to have positive perception toward elderly. Similarly, although there is an insignificant association between level of knowledge and level of perception, those nursing students who regarded themselves with a positive perception were among those who have a higher knowledge level about self-neglect in elderly. However, there still a need to increase the nursing students’ awareness and improve their knowledge and perception regarding this issue as they will be more knowledgeable and skilful in delivering a good and quality care towards the elderly.